Eco-synthesis of gold nanoparticles by Sericin derived from Bombyx mori silk and catalytic study on degradation of methylene blue. (17th February 2021) - Harisha, K. S.; Parushuram, N.; Asha, S.; Suma, S. B.; Narayana, B.; Sangappa, Y.
Abstract: In recent years, the eco-friendly synthesis of noble metal nanoparticles using bio-resources has given rise to a new trend in nanoscience and nanotechnology. In the present work, well-dispersed gold nanoparticles (AuNPs) are synthesized by redox of chloroauric acid (HAuCl4 .H2 O) using Silk Sericin (SS) obtained from Bombyx mori cocoons. The selection of SS, a textile industry waste, as a bio template is mainly due to its dual action as a metal ion reduction and stabilizer of the formed nanoparticles. The formed AuNPs are characterized by a transverse peak in the wavelength range λ  = 530–540 nm in the UV–visible spectra and characteristic Bragg's reflections observed in the XRD profile. The transmission electron microscopy (TEM) indicates the evolution of spherical AuNPs with the radii of individual particles in the range of 5–15 nm. The X-ray photoelectron spectroscopy (XPS) study showed two distinct peaks separated by 3.65 eV are observed due to the splitting of the Au4f level. Further, the potential catalytic action of the AuNPs is evaluated on the reduction of Methylene blue (MB). The study confirms the degradation of MB as a function of AuNPs concentration. Almost all the MB dye degrades in the highest AuNPs concentration.